The correction of occlusal vertical dimension on tooth wear - Rostiny Rostiny (Dental Journal (Majalah Kedokteran Gigi), 2007)
The loss of occlusal vertical dimension which is caused by tooth wear is necessarily treated to regain vertical dimension. Correctional therapy should be done as early possible. In this case, simple and relatively low cost therapy was performed. In unserve loss of occlusal vertical dimension, partial removable denture could be used and the improvement of lengthening anterior teeth using composite resin to improve to regain vertical dimensional occlusion.